EFFICACY OF 3% HYPERTONIC SALINE VS 20% MANNITOL IN REDUCING CEREBRAL OEDEMA OF NONTRAUMATIC ETIOLOGY IN PICU ADMITTED CHILDREN: A COMPARATIVE OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To compare the efficacy and safety of 3% hypertonic saline and mannitol in children with cerebral edema. Methods: This observational study was conducted in the PICU of a tertiary care hospital, including 60 children (3 months-14 years) with non-traumatic cerebral edema, PT INR ≤1.5, and at least one reactive pupil. Exclusion criteria included seizure disorders, hepatic encephalopathy, anoxic spells, cerebral malaria, renal dysfunction, intracranial bleed, and renal failure. Participants were divided into two groups by simple randomization; Group A (n = 30) received mannitol, while Group B (n = 30) was treated with 3% saline. MAP, serum electrolytes, osmolality were monitored and neurological status was assessed using the GCS. Results: The mean age was comparable between groups. Fever was the most common symptom and meningoencephalitis was the leading cause of cerebral edema. Group B showed significantly faster improvement in GCS scores at 12, 24, and 48 hours. The duration of coma was significantly shorter in Group B (48.43 ± 18.61 hrs) than Group A (71.50 ± 17.59 hrs; p = 0.001). Serum sodium and chloride levels increased in Group B but remained within safe limits. No significant differences were observed in potassium, renal function markers, osmolality, or mortality between the groups. Conclusion: 3% hypertonic saline was found to be more effective than mannitol in improving neurological outcomes in children with non-traumatic cerebral edema, without adverse effects. It may be a preferred choice in patients with hypotension.